RANCANG BANGUN SISTEM INFORMASI EKSTRAKURIKULER BERBASIS WEB (Studi Kasus: SMA Negeri 6 Bekasi) - Imara Acacia Khalda (2020)
SMA Negeri 6 Bekasi is one of the State High Schools in Bekasi, which has an extracurricular activity as a goal to help develop the personality and abilities and interests and talents of students in achieving maximum results. SMA Negeri 6 Bekasi has 18 kinds of extracurricular activities that can be participated by all students. In the management and implementation of extracurricular activities, there are still some problems, namely the unpublished information regarding extracurricular achievements, the registration process and assessment data as well as data on activities that have not been computerized. So that the resulting data are not integrated and can cause errors, and duplication of data, this study aims to design online registration, attendance records for students who want to join extracurricular activities or have participated in extracurricular activities and design management data for achievement of extracurricular activities and student value data on extracurricular activities. The method used in this development uses a prototype method which includes data collection, system design, coding using PHP programming language and testing. The expected results in this study are the creation of a web-based extracurricular information system that can improve school performance and help coaches manage extracurricular activities more easily to support students' abilities to develop more.